Long-term performance and durability of lime-stabilized oil-contaminated soils - Hadis Nasiri; Navid Khayat; Ahad Nazarpour (Heliyon)
In oil-rich regions, the increasing risk of oil spills on soil is largely attributed to intensified extraction and transportation activities. This situation necessitates a focus on the short-term and long-term strength of contaminated soils. While existing literature primarily evaluates the oil-contaminated soils over short-term periods, typically up to 28 days, it is essential to investigate their long-term performance, extending the evaluation period to 365 days. This study addresses the critical gap in understanding the long-term performance of soils contaminated with 4 %, 7 %, and 10 % oil by evaluating the effectiveness of lime stabilization over a one-year period. Laboratory tests were conducted on soils treated with varying lime contents (0 %, 3 %, 6 %, and 9 %) and cured for 1, 14, 28, and 365 days. Key performance indicators, including unconfined compressive strength (UCS), California Bearing Ratio (CBR), and durability under wet-dry cycles, were measured. The results demonstrate that a 6 % lime content significantly improves long-term UCS, with strength gains ranging from 16.6 % to 24.5 % while enhancing resilience to wet-dry cycles. Microstructural analyses confirmed the formation of calcium-aluminum-silicate-hydrate (C-A-S-H) phases, contributing to the observed strength and durability improvements. This research underscores the potential of lime stabilization as a sustainable solution for managing oil-contaminated soils, reducing reliance on raw materials, and promoting more sustainable infrastructure development.